2021
DOI: 10.1371/journal.pone.0247977
|View full text |Cite
|
Sign up to set email alerts
|

Costs and cost-effectiveness of management of possible serious bacterial infections in young infants in outpatient settings when referral to a hospital was not possible: Results from randomized trials in Africa

Abstract: Introduction Serious bacterial neonatal infections are a major cause of global neonatal mortality. While hospitalized treatment is recommended, families cannot access inpatient treatment in low resource settings. Two parallel randomized control trials were conducted at five sites in three countries (Democratic Republic of Congo, Kenya, and Nigeria) to compare the effectiveness of treatment with experimental regimens requiring fewer injections with a reference regimen A (injection gentamicin plus injection proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The cost of local assembly of CDK ($2.20) compared to the lowest average patient cost of treating blood stream infection in neonates in Africa ($20.90) [45] buttresses the cost-effectiveness of a clean delivery kit in preventing infections in these settings. Assessment of clean delivery kit acceptability among the TBAs revealed that the kits were perceived as acceptable, appropriate, and essential items in ensuring clean deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of local assembly of CDK ($2.20) compared to the lowest average patient cost of treating blood stream infection in neonates in Africa ($20.90) [45] buttresses the cost-effectiveness of a clean delivery kit in preventing infections in these settings. Assessment of clean delivery kit acceptability among the TBAs revealed that the kits were perceived as acceptable, appropriate, and essential items in ensuring clean deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…In the current PLoS One Neonatal Infection Collection, Garg and colleagues [ 27 ] estimated the costs of treating young infants with PSBI as outpatients when a referral is not possible in low-resource settings using the data from African Neonatal Sepsis Trials (AFRINEST) [ 10 , 11 ]. The weighted average costs across all sites for treating clinical severe infection in 2012 were US$ 25.3 (95% CI US$ 20.4–30.1) per infant treated when the regimen with 7 days of gentamicin plus amoxicillin was used, and US$ 20.9 (95% CI US$16.4–25.3) when the regimen with 2 days gentamicin plus 7 days amoxicillin was used.…”
Section: Discussionmentioning
confidence: 99%
“…The health system will have a reduced load as issues with quality of care at the hospitals, limited hospital beds, overburdened staff, non-functional equipment, regular supply of commodities, and patient satisfaction are common challenges [ 41 , 42 ], especially in low resource settings. The cost of outpatient treatment is much less than inpatient treatment [ 27 , 43 ]. Moreover, there is less risk of nosocomial infections with outpatient treatment [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%